Implementing STEM-based learning to support health programs at MI Muhammadiyah Paremono - Nugroho, Irham; Syarifuddin, Alfian; Khasmi, Charistya Aja; Sugesti, Abid Nur; Oktaviyani, Tiwi; Nofariyanto, Haris (Universitas Muhammadiyah Magelang, 2025)
The adoption of Clean and Healthy Living Behaviors (CHLBs) at MI Muhammadiyah Paremono remains a challenge, primarily due to students' low awareness of hygiene, minimal health practices within the school environment, and limited access to interactive learning media. This community engagement program aimed to enhance students' understanding and adoption of CHLBs through a Science, Technology, Engineering, and Mathematics (STEM) approach. The activities included developing a STEM-based health module, providing teacher training, socializing CHLBs among students, and promoting hygiene practices within the school environment. Learning was delivered interactively through experiments and project-based methods, such as a handwashing simulation using pepper powder to represent germs and the use of the HealthHeroes application to assess the nutritional value of food. The program's effectiveness was evaluated through observation, pre-tests and post-tests, and satisfaction surveys for teachers and students. The results showed a significant average increase of 35.2% in students' understanding of CHLBs, along with an improvement in their hygiene-related behaviors. Teachers also reported feeling more confident in delivering STEM-based health education. As a follow-up, the school will receive a self-evaluation guide and continuous support to ensure CHLB practices are embedded in the school culture. This program is expected to create a sustainable positive impact on health and hygiene within the school environment.